ANALISIS SEDIMENTASI PADA MUARA SUNGAI KOMERING KOTA PALEMBANG - KURNIA OKTAVIA USMAN (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2014)
Komering River is a river with huge potential as flood controlling. The main purpose of this study is to analyze the value of sediment load in the estuary of Komering river. In this study, was used four methods to analyze the total sediment discharge in the estuary of Komering river in Palembang is the method of Yang, Englund Hansen, Bagnold and Methods Laursen. The method of Yang obtained for Qt is 148,32 lb/s. The method of Englund and Hansen obtained for Qt is 181,47 lb/s. The method of Bagnold obtained for Qt is 122,27 lb / s and the method of Laursen obtained for Qt is 20,32 lb/s. In these calculations the most appropriate method of Bagnold, it has the smallest percentage difference between Qt and Qt field calculations is 10,43 %. Keywords : Bed load Sediment, Sedimentation, Estuary of Komering river